1991
DOI: 10.1143/jjap.30.1670
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of HoBa2Cu3O7-x-La1.5Ba1.5Cu3O7-y-HoBa2Cu3O7-x Junctions with Planar-Type Structures

Abstract: A HoBa2Cu3O7-x -La1.5Ba1.5Cu3O7-y -HoBa2Cu3O7-x junction having a planar structure is fabricated and its electrical characteristics are investigated. The planar junction is formed by sectioning a HoBa2Cu3O7-x layer into two superconducting electrodes keeping a submicrometer between them. Supercurrent is detected for the junction with an electrode spacing smaller than 0.4 µm. Critical current is exponentially dependent on electrode spacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Experimentally, proximity effect was found to be weaker in the c-axis direction than in the ab-plane direction due to a much shorter co-herence length in the former direction. [89][90][91] We note, however, that so-called giant proximity effect has been reported both in the ab-plane [92][93][94][95] and c-axis 96 directions. Proximity effect in HTSC-ferromagnet and/or HTSC-half-metal heterostructures have also been studied experimentally.…”
Section: Summary and Experimental Implicationsmentioning
confidence: 57%
“…Experimentally, proximity effect was found to be weaker in the c-axis direction than in the ab-plane direction due to a much shorter co-herence length in the former direction. [89][90][91] We note, however, that so-called giant proximity effect has been reported both in the ab-plane [92][93][94][95] and c-axis 96 directions. Proximity effect in HTSC-ferromagnet and/or HTSC-half-metal heterostructures have also been studied experimentally.…”
Section: Summary and Experimental Implicationsmentioning
confidence: 57%
“…[6,7]. Barholz et al [18] observed no supercurrent in coplanar junctions with trenches down to 50 nm; they ascribed previous findings [4,5,10] to HTS microshorts formed by inadvertent resputtering of YBa 2 Cu 3 O 7 (YBCO). Yoshida [19] revisited ab-plane step-edge junctions with YBCO electrodes and Co-doped PBCO as the barrier; he found that n 6 A, which is 2 orders of magnitude less than what was claimed before.…”
mentioning
confidence: 97%
“…While in this Letter we have considered barriers up to 200 Å thick, the supercurrent was sizeable, and it is clear that the maximum coupling distance should be at least several times larger, even in our c-axis geometry-and conceivably longer in the more favorable a-axis geometry (as in Refs. [4][5][6][7][8][9][10][11]). …”
mentioning
confidence: 99%
“…Indeed, numerous groups have demonstrated a high T c proximity effect with insulating cuprates [34,35,36,37,38], Au quantum dots [39], and in LCMO/YBCO thin films [40,41,42,43]. Recently we were able to achieve a proximity effect between Bi 2 Sr 2 CaCu 2 O 8+δ [44] and two heavily doped topological insulators (Bi 2 Se 3 , Bi 2 Te 3 ), which are known to superconduct with heavy doping [45,46] or pressure [47].…”
Section: Introductionmentioning
confidence: 99%